Differential Plasma Metabolites between High- and Low-Grade Meningioma Cases - Kurokawa, Gabriel A. [UNESP]; Hamamoto Filho, Pedro T. [UNESP]; Delafiori, Jeany; Galvani, Aline F. [UNESP]; de Oliveira, Arthur N.; Dias-Audibert, Flávia L.; Catharino, Rodrigo R.; Pardini, Maria Inês M. C. [UNESP]; Zanini, Marco A. [UNESP]; Lima, Estela de O. [UNESP]; Ferrasi, Adriana C. [UNESP] (MDPI, 2023)
Meningiomas (MGMs) are currently classified into grades I, II, and III. High-grade tumors are correlated with decreased survival rates and increased recurrence rates. The current grading classification is based on histological criteria and determined only after surgical tumor sampling. This study aimed to identify plasma metabolic alterations in meningiomas of different grades, which would aid surgeons in predefining the ideal surgical strategy. Plasma samples were collected from 51 patients with meningioma and classified into low-grade (LG) (grade I; n = 43), and high-grade (HG) samples (grade II, n = 5; grade III, n = 3). An untargeted metabolomic approach was used to analyze plasma metabolites. Statistical analyses were performed to select differential biomarkers among HG and LG groups. Metabolites were identified using tandem mass spectrometry along with database verification. Five and four differential biomarkers were identified for HG and LG meningiomas, respectively. To evaluate the potential of HG MGM metabolites to differentiate between HG and LG tumors, a receiving operating characteristic curve was constructed, which revealed an area under the curve of 95.7%. This indicates that the five HG MGM metabolites represent metabolic alterations that can differentiate between LG and HG meningiomas. These metabolites may indicate tumor grade even before the appearance of histological features.
Keywords: biomarkers; grading; meningioma; metabolomics; plasma samples; screening